Selective interaction of JNK protein kinase isoforms with transcription factors. - Gupta, S (1996)
The JNK protein kinase is a member of the MAP kinase group that is activated in response to dual phosphorylation on threonine and tyrosine. Ten JNK isoforms were identified in human brain by molecular cloning. These protein kinases correspond to alternatively spliced isoforms derived from the JNK1, JNK2 and JNK3 genes. The protein kinase activity of these JNK isoforms was measured using the transcription factors ATF2, Elk-1 and members of the Jun family as substrates. Treatment of cells with interleukin-1 (IL-1) caused activation of the JNK isoforms. This activation was blocked by expression of the MAP kinase phosphatase MKP-1. Comparison of the binding activity of the JNK isoforms demonstrated that the JNK proteins differ in their interaction with ATF2, Elk-1 and Jun transcription factors. Individual members of the JNK group may therefore selectively target specific transcription factors in vivo.